2020
DOI: 10.1111/jocs.14754
|View full text |Cite
|
Sign up to set email alerts
|

Four pathways for hydatid pulmonary embolism

Abstract: Introduction Hydatid pulmonary embolism (HPE) is rare but remains an etiology that needs to be considered and kept in mind, especially in endemic areas, as regards nonthrombotic embolism. Methods Between 2000 and 2014, 10 patients were treated in our department for the presence of hydatid material in the pulmonary arterial circulation. Through these 10 cases, we try to assess the radioclinical characteristics and results of the surgical treatment. Results The study included six men and four women, average age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Primary renal hydatic cyst is very rare and has been mostly reported in association with hepatic, pulmonary, or multi-organ hydatidosis. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary renal hydatic cyst is very rare and has been mostly reported in association with hepatic, pulmonary, or multi-organ hydatidosis. 2 …”
Section: Discussionmentioning
confidence: 99%
“…it is a neglected zoonosis, caused by cestode larvae called Echinococcus granulosus and is still endemic in many rural areas in North Africa, the Middle East, South America, Australia, New Zealand, Alaska, and northern China. 1 , 2 In Morocco, the prevalence of this pathology in humans is underestimated with an annual increase in the number of cases. 3 …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that echinococcosis of the pulmonary artery is mainly derived from hepatic hydatid cysts, and when these rupture in the liver or other organs in the abdomen, they invade the inferior vena cava or the hepatic vein. This enables the cyst contents to enter into the blood circulation and cause a pulmonary embolism after entering into the pulmonary artery and its branches through the right atrium and right ventricle [ 4 6 ]. By the time this situation occurs, the hydatid cyst is not usually seen in the right atrium or right ventricle, and most patients will have a history of hepatic hydatid disease.…”
Section: Discussionmentioning
confidence: 99%